MRI inflammation of the hand interosseous tendons occurs in anti-CCP-positive at-risk individuals and may precede the development of clinical synovitis. Issue 6 (23rd June 2019) - Mankia, Kulveer; D'Agostino, Maria-Antonietta; Rowbotham, Emma; Hensor, Elizabeth MA; Hunt, Laura; Möller, Ingrid; Miguel, Misabel; Mérida-Velasco, José Ramon; Murillo-González, Jorge; Naredo, Esperanza; Nam, Jacqueline Leong; Tan, Ai Lyn; et al.
Abstract : Interosseous tendon inflammation (ITI) has been described in rheumatoid arthritis (RA). Whether ITI occurs in at-risk individuals before the onset of clinical synovitis is unknown. Objectives: To investigate, by MRI, ITI in anti-cyclic citrullinated peptide (CCP)-positive at-risk individuals (CCP +at risk) and to describe the anatomy, prevalence and clinical associations across the RA continuum. Methods: Hand MRI was performed in 93 CCP + at risk, 47 early RA (ERA), 28 established 'late' RA (LRA) and 20 healthy controls (HC) and scored for ITI, flexor tenosynovitis (TSV) and RA MRI scoring at the metacarpophalangeal joints (MCPJs). Cadaveric and histological studies were performed to explore the anatomical basis for MRI ITI. Results: The proportion of subjects with ITI and the number of inflamed interosseous tendons (ITs) increased along the disease continuum (p<0.001): 19% of CCP +at risk, 49% of ERA and 57% of LRA had ≥1 IT inflamed . ITI was not found in any HC. ITI was more frequently identified in tender MCPJs compared with nontender MCPJs (28% vs 12%, respectively). No IT tenosynovial sheath was identified in cadavers on dissection or histological studies suggesting MRI findings represent peritendonitis. Dye studies indicated no communication between the IT and the joint. Conclusions: ITI occurs in CCP + at-risk individuals and can precede the onset of clinical synovitis. The ITs may be important nonsynovial extracapsular targets in the development and progression of RA.